Multi-frequency dual-polarized platform for validation of satellite precipitation measurements - Vega, Manuel A., author; Chandrasekar, V., advisor; Jayasumana, Anura, committee member; Cheney, Margaret, committee member; Mielke, Paul, committee member (Colorado State University. Libraries, 2017)
Satellite missions such as the Tropical Rainfall Measuring Mission (TRMM) and the Global Precipitation Measurement (GPM) mission have demonstrated the value of rainfall measurements at a global scale. Both missions use a multi-frequency, active/passive (i.e. radar/radiometer) suite of instruments to achieve their measurement goals. Calibration and validation of these instruments has a vital role in the success of the mission since quantitative characterization of precipitation is the primary goal. Furthermore, these missions have also extended the understanding of the synergy between radar/radiometer observations within the atmospheric science community. From a ground validation (GV) perspective, active/passive observations are typically achieved with co-located, but independent instruments. In some cases, this has introduced radio frequency interference (RFI) between adjacent active/passive frequencies of operation, asynchronous scanning strategies and unmatched observation volumes. The work presented focuses on the following topics: 1) engineering aspects in the design of an active/passive remote sensing platform, 2) the design of a solid-state, dual-polarized, multi-frequency, Doppler radar system and performance characterization and 3) calibration approach for a ground based, multi-frequency, radar/radiometer system and first calibrated observations in this mode of operation.
Keywords: dual-polarized; radar; multi-frequency; Doppler